Factors predicting intention to engage in advance care planning among patients with chronic kidney disease in Thailand: A cross-sectional study - Kanokwan Linthong; Yaowarat Matchim; Piyawan Kanan; Thatsanee Poosumang (Belitung Nursing Journal, 2026)
Background: Chronic kidney disease (CKD) is a progressive condition associated with declining decisional capacity and increased end-of-life care needs. Although advance care planning (ACP) supports patient autonomy and goal-concordant care, engagement remains limited, particularly among patients with pre-dialysis CKD in Thailand. Objectives: To assess the level of intention to engage in ACP and identify factors predicting ACP intention among patients with CKD stages 3–5 in Thailand. Methods: A cross-sectional study was conducted from April to June 2025 among 184 patients aged ≥20 years with CKD stages 3–5 attending nephrology outpatient clinics at five public tertiary-level hospitals. Participants were recruited through purposive sampling using a multistage approach. Data were collected using validated questionnaires and analyzed using descriptive statistics and hierarchical multiple regression. Results: The mean age of participants was 64.48 years (SD = 11.78), and 51.6% were female. The level of intention to engage in ACP was low (M = 16.89, SD = 7.83). Hierarchical regression analysis identified attitudes toward ACP (β = 0.296, p < 0.001), family support (β = 0.220, p = 0.001), perceived self-efficacy in self-management (β = 0.155, p < 0.05), and knowledge of ACP (β = 0.145, p < 0.05) as significant predictors. The final model explained 56.6% of the variance in ACP intention (R² = 0.566), with the independent variables contributing an additional 33.3% beyond demographic and clinical variables (ΔR² = 0.333, p < 0.001). Death anxiety was not a significant predictor. Conclusions: ACP intention among Thai patients with CKD was low, influenced by attitudes, family support, self-efficacy, and ACP knowledge. Nurses should implement family-centered, empowerment-based educational interventions and integrate ACP discussions into routine nephrology care to promote timely and culturally aligned end-of-life decision-making.